2019
DOI: 10.1002/cam4.2630
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effect of icaritin on prostate cancer via regulating miR‐381‐3p and its target gene UBE2C

Abstract: Prostate cancer (PCa) is one of the most common health‐related issues in the male individuals of western countries. Icaritin (ICT) is a traditional Chinese herbal medicine that exhibits antitumor efficacy in variety of cancers including PCa. However, the precise function and detailed molecular mechanism of ICT in the regression of PCa remain unclear. Ubiquitin‐conjugating enzyme E2C (UBE2C) is an anaphase‐promoting complex/cyclosome (APC/C)‐specific ubiquitin conjugating enzyme, which acts as an oncogene in PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 43 publications
0
44
0
Order By: Relevance
“…For instance, miR-381-3p overexpression promotes cancer cell proliferation in glioblastoma cells and osteosarcoma cells by targeting the brain relative specific expression gene LRRC4 (Tang et al, 2011;Li et al, 2016). On the contrary, miR-381-3p functions as a tumor suppressor gene in rectal cancer and prostate cancer through suppression of UBE2C (Zhang et al, 2018;Hu et al, 2019). Through a cellbased screening for miRNAs regulating apoptosis, we found that miR-381-3p negatively regulates TNF-induced apoptosis in multiple human cancer cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…For instance, miR-381-3p overexpression promotes cancer cell proliferation in glioblastoma cells and osteosarcoma cells by targeting the brain relative specific expression gene LRRC4 (Tang et al, 2011;Li et al, 2016). On the contrary, miR-381-3p functions as a tumor suppressor gene in rectal cancer and prostate cancer through suppression of UBE2C (Zhang et al, 2018;Hu et al, 2019). Through a cellbased screening for miRNAs regulating apoptosis, we found that miR-381-3p negatively regulates TNF-induced apoptosis in multiple human cancer cell lines.…”
Section: Discussionmentioning
confidence: 96%
“…In addition, recent studies have shown that miR-381 has a very important role in tumor oncogenesis, development, metastasis and chemical resistance. For example, miR-381 inhibits the proliferation and invasion of prostate cancer cells via the regulation of UBE2C [41]; miR-381 inhibits lung adenocarcinoma progression by directly targeting LMO3 through the regulation of the PI3K/Akt signaling pathway and EMT [42]; up-regulation of miR-381 inhibits the NAD + salvage pathway and promotes apoptosis in breast cancer cells [43]; miR-381 overcomes cisplatin resistance in breast cancer cells by targeting MDR1 [44]. In line with these findings, metformin upregulated the level of miR-381 to inhibit NSCLC tumor growth and metastasis in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies revealed the anti-inflammatory and anti-survival activities of ICT in various cancer types including PCa 15 , 16 , 18 - 20 . It is established that HFD-induced obesity is a well-known risk factor for the development of various diseases, including cancer, through regulatory mechanisms 2 , 21 .…”
Section: Discussionmentioning
confidence: 99%